Anisotropic dense collagen hydrogels with two ranges of porosity to mimic the skeletal muscle extracellular matrix - Camman, Marie; Joanne, Pierre; Brun, Julie; Marcellan, Alba; Dumont, Julien; Agbulut, Onnik; Hélary, Christophe (Biomaterials advances, 2023)
Despite the crucial role of the extracellular matrix (ECM) in the organotypic organization and function of skeletal muscles, most 3D models do not mimic its specific characteristics, namely its biochemical composition, stiffness, anisotropy, and porosity. Here, a novel 3D in vitro model of muscle ECM was developed reproducing these four crucial characteristics of the native ECM. An anisotropic hydrogel mimicking the muscle fascia was obtained thanks to unidirectional 3D printing of dense collagen with aligned collagen fibrils. The space between the different layers was tuned to generate an intrinsic network of pores (100 μm) suitable for nutrient and oxygen diffusion. By modulating the gelling conditions, the mechanical properties of the construct reached those measured in the physiological muscle ECM. This artificial matrix was thus evaluated for myoblast differentiation. The addition of large channels (600 μm) by molding permitted to create a second range of porosity suitable for cell colonization without altering the physical properties of the hydrogel. Skeletal myoblasts embedded in Matrigel®, seeded within the channels, organized in 3D, and differentiated into multinucleated myotubes. These results show that porous and anisotropic dense collagen hydrogels are promising biomaterials to model skeletal muscle ECM.